El nacimiento de un observador social Charles Darwin en San Salvador de Bahía (29/2-18/3/1832) - Arana Bustamante, Luis (2019)
This article, first of two projected about Darwin in Brazil, starts the examination of the making of Charles Darwin as social —and sociological— observer through examination of his first contact with South American social realities in San Salvador de Bahia, Brazil. It can be said that this process, not much studied in Darwinian research, begun in Brazil, notwithstanding the more or less brief residence of the British naturalist in this country (four months and three days between February and July, 1832). Brazilian historiography has not researched Darwin’s presence in this country because his plain opinions against the slavery system. We used the Beagles’s Diary (Darwin [1831-1836]), as principal historical source in this aspect of our Darwin research.